PENGARUH SALINITAS TERHADAP SERANGAN PENGGEREK KAYU DI LAUT PADA BEBERAPA JENIS KAYU - Mohammad Muslich; Ginuk Sumarni (Jurnal Penelitian Hasil Hutan, 1987)
Marine  borers are wood destroying  organisms  living in the sea, brackish  and estuarine  water. Environmental   conditions  such as salinity, pollution  and temperature  of  the sea water influence  the activities  and precence  of  marine  borers.One hundred pieces of wood from  five  species had been exposed  to marine borers in four  different  salinities for  nine months. The test sites chosen were around  Gulf  of Jakarta  i.e.  about 3 km off  shore, and at three  locations  along  a canal of  brackish fishpond,  respectively  in the estuary,  1  km  and 2 km from the shore.The result shows that at the sea site where the salinity  is relatively stable around 29 ‰ – 30‰ ,  all of the wood tested are badly attacked  by Mollusc  belonging  to the species of Martesia  striata  Linne.,  Dicyathifer  manni  Wright.,  and  Bankia  campanellata  Moll/Roch.    Along  the canal where the salinity is between 5‰-30‰, damage is only small.  The result also shows no sign of attack on all samples exposed  along the canals, although  the salinity is not significantly  different  from that of  the estuary.